Effect of Embryonic Cerebrospinal Fluid on Proliferation and Differentiation of Neuroprogenitor Cells - Yari, Siamak (Royan Institute, 2013)
OBJECTIVE: Embryonic cerebrospinal fluid (e-CSF) has an important role in development of embryonic and adult brain. Proteomic analysis suggests that this fluid has many morphogenes and cytokines that alter in time and space throughout embryonic life. The aim of this study was to evaluate the developmental effect of embryonic CSF on proliferation and differentiation of neuroprogenitor cells in different gestational age. MATERIALS AND METHODS: In this In this experimental study, we examined the role of e- CSF on proliferation and differentiation of neuroprogenitor cells using neurosphere culture method. Neurospheres size analysis and MTT assay were used to assess cell proliferation after four days in vitro. Glial differentiation study was carried out by immunocytochemistry. Neurospheres size and percentage of glial fibrialy acidic protein (GFAP) positive cells were measured by image analyzer (image J). The data were analyzed by one-way ANOVA, followed by the Tukey’s post hoc test. Data were expressed as mean ± SEM, and differences were considered significant when p<0.05, 0.01 and 0.001. RESULTS: Viability and proliferation of neuro progenitor cells in cultures conditioned with E16 CSF and E18 CSF were significantly increased compare to control group. A dramatic decrease in percentage of GFAP-positive cells was found following the application of CSF from E16 and E18 embryos, but not E20 CSF. CONCLUSION: Our data suggest that, e-CSF altered proliferation and differentiation of neuro progenitor cells in age dependent manner. E16 and E18 CSF enhanced proliferation and viability of neuro progenitor cells, and inhibited differentiation to glial fate in comparison with control group.